Gestión administrativa y desempeño laboral en la Gerencia Sub Regional de Ucayali Contamana 2023 - Acho Cavero de Gomez, Rene Marianela (2024)
The purpose of this study was to establish the relationship between administrative management and work performance in the Sub Regional Management of Ucayali - Contamana in the year 2023. A descriptive correlational approach was used, through a non-experimental design. The sample consisted of 127 administrative workers selected from a population of 190 employees. A questionnaire was applied to them to collect the necessary information. The results revealed that administrative management was evaluated as fair (29%) and employees' work performance as average (27%). Furthermore, a positive and significant relationship was found between administrative management and job performance, supported by a correlation coefficient of r=0.861 and a significance of p=0.000. Likewise, the planning dimension shows a coefficient and significance of (r= Rho=0.773; p=0.000); Also, the organization dimension presents a (r= Rho=0.726; p=0.000); for the direction dimension (r= Rho=0.676; p=0.000); and the control dimension shows a coefficient and sig, of (r= Rho=0.639; p=0.000) all these results are positively and significantly related to job performance in the Sub Regional Management of Ucayali – Contamana